Akuntabilitas Pelayanan Publik Dinas Tenaga Kerja Kabupaten Buton - Masri, Febby; Abidin, Zainul; Didi, La (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study aims to describe public service accountability at the Buton Regency Manpower Office. This research uses a descriptive method with a qualitative approach. Data was collected using interview, observation and documentation techniques. The results showed that public service accountability at the Manpower Office that in organising passport recommendation services for Prospective Indonesian Migrant Workers (CPMI) has worked in accordance with references and laws and regulations and other regulations governing technical and administrative requirements. In dealing with obstacles that occur to service users, it is very responsive and the priority of the interests of service needs is quite well met with the discipline of the presence of service officers and the behaviour of officers in providing services. However, there are still some weaknesses that must be improved in service references such as service standards that have not been updated according to the latest provisions as well as in the aspect of prioritising the interests of service users in terms of providing facilities and infrastructure in handling complaints and facilities that are still limited in supporting service activities.